Foraging Pattern, Functional and Numerical Response of Coccinella Septempunctata (L.) Feeding on Myzus Persicae (Sulzer.) - Khan, Muhammad Rahim (2003)
The prey searching pattern, fimctional and numerical response of Coccinella septempunctata (L.), common ladybird beetle. feeding on Myzus persicae (Sulzer). green peach aphid, were studied to evaluate predation potential. Impact of some potential abotic (viz, temperature) and biotic (viz prey size, prey distribution, predations hunger level and physical heterogeneity among host plant species) factors on the above parameters were studied in the laboratory and semi-field conditions. Both larvae and adult of C. septempunctata selected from single stock culture were found to detect their prey by physical contact. Their initial search was random which subsequently become prey-oriented. The prey search path indicated three distinct phases of search. viz "extensive search", initially "intensive search" on encountering the prey, and "post-intensive search" following ingestion of a prey. The intensity of search rate significantly increased following first prey intake stimulus. Predators, hunger level also influenced search pattern. Both prey size and prey densities influenced prey consumption of the predator. The rate of successful encounter and ultimate consumption also depended on the age/stages of the predator. The fourth instar larvae were found more voracious among larval stages consuming about 69-75 aphidsll2 hours. Interestingly, adult females always consumed more aphids than the male counterpart average being 78.5 aphidsl12 hours. The interaction among prey density, prey size and predator'S age were all significant (P<O.OI) having profound impact on each other. Functional response curves ranged from linear to sigmoid and increase polynomial. Temperature variation had affected all the components viz. instantaneous attack rate (a'), prey handling time (Tn). given up time etc. of prey searching capacity of the predator. The lower threshold temperature where the predators start feeding was 10°C and with initial increase in ambient temperature the predation rate increased upto a level beyond which the intensity of predation gradually diminished and at the upper threshold (38'C) the predators evantua1ly stopped feeding. The foraging activity took place within the range of 10-40'C, and maximum was between 20'23'C (predicted) and 23-25'C (observed).